Identifying the problem weeds of rice-based systems along the inland-valley catena in the southern Guinea Savanna, Africa - Touré, A.; Rodenburg, J.; Marnotte, P.; Dieng, I.; Huat, J. (Wiley, 2014)
While weeds generally are considered as the most important overarching production constraints in inland-valley cropping systems in West Africa, little is known about species' associations with environmental and crop management factors. Weed species' associations with seasonal and environmental factors, such as their position on the catena, soils and cropping systems, were studied during two seasons (dry and wet) in 45 arable fields of three inland valleys in south-western Benin, Africa. The three most dominant weed species were Dactyloctenium aegyptium, Commelina benghalensis and Digitaria horizontalis on the inland-valley crests (uplands), Ludwigia hyssopifolia, Corchorus aestuans and Ludwigia octovalvis on the sloping hydromorphic fringes and Leersia hexandra, Ipomoea aquatica and Fimbristylis ferruginea in the valley bottoms (lowlands). Echinochloa colona, Cleome viscosa and Talinum triangulare were the three most dominant species in the dry-season crops (maize or vegetables) and Leer. hexandra, I. aquatica and Sphenoclea zeylanica were the three most dominant species in the wet-season crop (rice). Ageratum conyzoides, Synedrella nodiflora and D. horizontalis were observed throughout the catena. Problem weeds in inland-valley agro-ecosystems are those that combine a high frequency with a high submergence tolerance and ecological plasticity, C4 grasses, perennial C3 species with persistent root structures and broad-leaved species with high propagation rates. Weed management strategies that are aimed at increasing the resilience of rice-based cropping systems in the inland valleys of the southern Guinea Savanna of Africa should address the categories of problem species that were identified in this study. This can be done best by following an integrated approach, including the use of more weed-competitive cultivars and rotation crops.